Improvement of crAssphage detection/quantification method and its extensive application for food safety - Lee, So-Young; Yang, Jihye; Lee, Ju-Hoon (Frontiers in Microbiology, 2023)
Water-borne diseases are usually caused by the fecal–oral transmission of human fecal pathogens. Traditionally, coliforms and enterococci are widely used as indicator bacteria, but they do not allow to differentiate between human and animal fecal contamination. Owing to its presence only in the human gut environment, crAssphage has been suggested as an alternative indicator of human fecal contamination to overcome the above challenges. In this study, 139 human and 89 animal fecal samples (e.g., chicken, cow, dog, pig, pigeon, and mouse) were collected. For the rapid detection of human crAssphage in fecal samples, quantitative real-time PCR (qPCR) was performed using five different oligonucleotide primer/probe combinations. These included three previously reported oligonucleotide primer/probe combinations (RQ, CPQ056, and CrAssBP) and two newly developed combinations (ORF00018-targeting CrAssPFL1 and ORF00044-targeting CrAssPFL2). The detection rate (crAssphage-positive rate) in human fecal samples were 23.0%, 30.2%, 28.8%, 20.1%, and 30.9%, respectively, suggesting CrAssPFL2 showed the highest detection rate. Furthermore, the lowest copy numbers (436.16 copy numbers) could be detected using the CrAssPFL2 combination. Interestingly, no difference in crAssphage detection rates was found between healthy people and intestinal inflammatory patients. As expected, no crAssphage was detected in any animal fecal samples, indicating its human specificity. Furthermore, qPCR analysis of sewage samples collected from five different sewage treatment plants revealed that they were all contaminated with 105.71 copy numbers/ml of crAssphage on average. The simulation test of crAssphage-contaminated food samples also confirmed that the detection limit was from 10 7.55 copy numbers of crAssphage in foods. Therefore, the newly developed and optimized qPCR would be useful for the sensitive detection of crAssphage while identifying the source of human fecal contamination.